2000
DOI: 10.1086/303088
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor FISH Analysis of Chromosomal Breaks, Duplications, Deletions, and Numerical Abnormalities in the Sperm of Healthy Men

Abstract: Transmitted de novo structural chromosomal abnormalities, the majority of which are paternally derived, can lead to abnormal reproductive outcomes as well as genetic diseases in offspring. We developed and validated a new multicolor FISH procedure (sperm ACM, which utilizes DNA probes specific for the alpha [1cen], classical, [1q12], and midi [1p36.3] satellites of chromosome 1) which utilizes DNA probes specific for three regions of chromosome 1 to detect human sperm that carry numerical abnormalities plus tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 75 publications
1
34
1
2
Order By: Relevance
“…A significant excess of sperm bearing partial duplications of the 9q region compared with those bearing partial duplications of 9cen (P Âź 0.017) was detected. In a similar study in control donors, 23 it was also observed that sperm carrying partial duplications and deletions of 1p were five times more frequent than those carrying 1cen structural abnormalities. Partial duplications and deletions may originate by: (1) structural rearrangements, (2) unequal crossover in meiosis I producing partial duplications and, (3) breakage events during meiosis.…”
Section: Discussionmentioning
confidence: 68%
“…A significant excess of sperm bearing partial duplications of the 9q region compared with those bearing partial duplications of 9cen (P Âź 0.017) was detected. In a similar study in control donors, 23 it was also observed that sperm carrying partial duplications and deletions of 1p were five times more frequent than those carrying 1cen structural abnormalities. Partial duplications and deletions may originate by: (1) structural rearrangements, (2) unequal crossover in meiosis I producing partial duplications and, (3) breakage events during meiosis.…”
Section: Discussionmentioning
confidence: 68%
“…Sloter et al 23 observed a slight trend toward higher frequencies of sperm with segmental duplications vs deletions in each man, regardless of age. Likewise, several authors [28][29][30] Age and sperm chromosome structural abnormalities C Templado et al showed that duplications of 1p were more frequent than deletions in human spermatozoa. The excess of duplications observed in sperm nuclei could be a reflection of the excess in acentric fragments described in sperm karyotypes.…”
Section: Discussionmentioning
confidence: 97%
“…Besides the laborious sperm karyotyping technique, the development of fluorescence in situ hybridization allows direct analysis of spermatozoa for numerical (and structural) aberrations in large numbers of sperm (Sloter et al, 2000).…”
Section: Paternal Age and Geneticsmentioning
confidence: 99%